The European Archaeological Expedition to Ed-Dur, Umm al-Qaiwayn (U.A.E.): An Interim Report on the 1987 and 1988 Seasons. Introduction - Boucherlat, R.
p.13-27: The Danish Excavations (D.T.Potts); p.29-56: Les fouilles françaises (?.Lecomte, R.Boucherlat, J.M.Culas); p.57- 69: The Belgian Excavations (E.Haerinck, K.G.Stevens); p.70-72: Bibliographie